Incommensurate spin-density-wave and metal-insulator transition in the one-dimensional periodic Anderson model - Bertussi, P. R.; Silva Neto, M. B.; Rappoport, T. G.; Malvezzi, André Luiz [UNESP]; dos Santos, R. R. (Amer Physical Soc, 2011)
We have used the density-matrix renormalization group method to study the ground-state properties of the symmetric periodic Anderson model in one dimension. We have considered lattices with up to N-s = 50 sites, and electron densities ranging from quarter to half filling. Through the calculation of energies, correlation functions, and their structure factors, together with careful extrapolations (toward N-s -> infinity), we were able to map out a phase diagram U vs n, where U is the electronic repulsion on f orbitals, and n is the electronic density, for a fixed value of the hybridization. At quarter filling, n = 1, our data is consistent with a transition at U-c1 similar or equal to 2, between a paramagnetic (PM) metal and a spin-density-wave (SDW) insulator; overall, the region U less than or similar to 2 corresponds to a PM metal for all n < 2. For 1 < n less than or similar to 1.5 a ferromagnetic phase is present within a range of U, while for 1.5 less than or similar to n < 2, we find an incommensurate SDW phase; above a certain U-c(n), the system displays a Ruderman-Kittel-Kasuya-Yosida behavior, in which the magnetic wave vector is determined by the occupation of the conduction band. At half filling, the system is an insulating spin liquid, but with a crossover between weak and strong magnetic correlations.